2018
DOI: 10.1103/physrevphyseducres.14.010139
|View full text |Cite
|
Sign up to set email alerts
|

Spatial thinking in astronomy education research

Abstract: This paper is part of the Focused Collection on Astronomy Education Research.] Multiple studies show that spatial thinking skills contribute to students' performance in science, technology, engineering, and mathematics disciplines. The study of astronomy is no different with the understanding of many astronomical phenomena requiring spatial thinking skills. This paper describes traditional and contemporary approaches to characterizing and measuring spatial thinking skills and suggests how they inform research … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
21
0
24

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(45 citation statements)
references
References 96 publications
0
21
0
24
Order By: Relevance
“…Previous work has found that students' spatial reasoning correlates with their understanding of lunar concepts [53,54]. Understanding of Moon phases also requires understanding the dynamic evolution of the phases over time and space [54], likely facilitated through interacting with and moving around a simulation. Furthermore, the traditional hands-on activity for teaching Moon phases (described below) is susceptible to various real-world inaccuracies, such as creating eclipses every month or rotating or orbiting the wrong way.…”
Section: Methodsmentioning
confidence: 99%
“…Previous work has found that students' spatial reasoning correlates with their understanding of lunar concepts [53,54]. Understanding of Moon phases also requires understanding the dynamic evolution of the phases over time and space [54], likely facilitated through interacting with and moving around a simulation. Furthermore, the traditional hands-on activity for teaching Moon phases (described below) is susceptible to various real-world inaccuracies, such as creating eclipses every month or rotating or orbiting the wrong way.…”
Section: Methodsmentioning
confidence: 99%
“…Spatial thinking has increasingly been identified as an important competency in different science disciplines [11,75] and astronomy is no different in this respect [1,10,[76][77][78]. Indeed, astronomy as a discipline seems to demand excellence in the ability to extrapolate three dimensionality in one's mind from one-or two-dimensional semiotic resources.…”
Section: The Multidimensionality Hierarchy and Extrapolating Threementioning
confidence: 99%
“…It is often taken for granted in astronomy education that students will be able to, in their minds, extrapolate a 3D experience from 1D and 2D representations. This is despite the growing body of research indicating that this is often not the case [1,11,78,[80][81][82][83]. For example, Parker and Heywood [82] found that students had great difficulty in moving from 2D representations of the solar system to 3D representations.…”
Section: The Multidimensionality Hierarchy and Extrapolating Threementioning
confidence: 99%
See 1 more Smart Citation
“…AER should also expand to new research topics. Spatial thinking in astronomy is an important area that would benefit from rigorous experimental research [5]. Student motivation and related constructs are also currently underdeveloped in the context of AER [14,16,17].…”
mentioning
confidence: 99%